2021
DOI: 10.21203/rs.3.rs-757239/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hesitancy Towards COVID-19 Vaccine Among Older People in Luzhou, China: A Cross-sectional Study

Abstract: Background:Vaccination is one of the most effective and low-cost health measures to prevent COVID-19. Vaccine hesitancy is an obstacle to COVID-19 vaccination. Objective:This study aims to inform the vaccine hesitancy and analyze related factors towards COVID-19 vaccination among elderly in Luzhou, so as to provide suggestions for increasing vaccines uptake. Methods:A face-to-face questionnaire cross-sectional survey was conducted among the elderly people over 60 years old in Luzhou City in April 2021 by multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…30 Other studies of vaccination intention specific to older adults showed intention rates varied widely from 52.7% to 91.3%. [31][32][33] The responses given for vaccination intention among Thai older adults may have been because this study was conducted during the third wave of the COVID-19 pandemic when the incidence of COVID-19 and mortality were increasing, particularly among older adults. As the perception of the severity of COVID-19 infection worsened, vaccination intention increased.…”
Section: Discussionmentioning
confidence: 99%
“…30 Other studies of vaccination intention specific to older adults showed intention rates varied widely from 52.7% to 91.3%. [31][32][33] The responses given for vaccination intention among Thai older adults may have been because this study was conducted during the third wave of the COVID-19 pandemic when the incidence of COVID-19 and mortality were increasing, particularly among older adults. As the perception of the severity of COVID-19 infection worsened, vaccination intention increased.…”
Section: Discussionmentioning
confidence: 99%